2013
DOI: 10.1038/nn.3494
|View full text |Cite
|
Sign up to set email alerts
|

Linear transformation of thalamocortical input by intracortical excitation

Abstract: Neurons in thalamorecipient layers of sensory cortices integrate thalamocortical and intracortical inputs. Although their functional properties can be inherited from the convergence of thalamic inputs, the roles of intracortical circuits in thalamocortical transformation of sensory information remain unclear. Here, by reversibly silencing intracortical excitatory circuits with optogenetic activation of parvalbumin-positive inhibitory neurons in mouse primary visual cortex, we compared visually-evoked thalamoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
159
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(193 citation statements)
references
References 60 publications
23
159
1
Order By: Relevance
“…Our model, however, makes predictions that can be tested with single neurons or pairs (Figs 8 and 9). One prediction, that recurrent connectivity is responsible for a large proportion of stimulus-tuned excitatory input, is consistent with findings from visual and auditory cortex that tuned recurrent excitation amplifies responses to thalamic input [46][47][48] . The fact that these responses are associated with slow dynamics 18 is also consistent with results from auditory cortex, suggesting that recurrent excitation prolongs response duration 48 .…”
Section: Discussionsupporting
confidence: 79%
“…Our model, however, makes predictions that can be tested with single neurons or pairs (Figs 8 and 9). One prediction, that recurrent connectivity is responsible for a large proportion of stimulus-tuned excitatory input, is consistent with findings from visual and auditory cortex that tuned recurrent excitation amplifies responses to thalamic input [46][47][48] . The fact that these responses are associated with slow dynamics 18 is also consistent with results from auditory cortex, suggesting that recurrent excitation prolongs response duration 48 .…”
Section: Discussionsupporting
confidence: 79%
“…4g, h). These results suggest that local connections contribute to the stimulus selectivity of L2/3 neurons by providing tuned excitation that modulates the membrane potential in a manner qualitatively similar to that observed in vivo [19][20][21][22][23] .…”
supporting
confidence: 57%
“…In mouse V1, a simple cell's subthreshold response to drifting grating stimuli [19][20][21][22][23] is characterized by two components that are determined by the angle and phase of the grating in relation to its RF (Fig. 4a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we revealed that the connectivity between L2/3 neurons in V1 is highly specific, though nonexclusive, with respect to their feature selectivity. Such a specific connection scheme may serve to amplify the incoming thalamic signal by providing strong excitation that is closely matched to thalamocortical input (7)(8)(9).…”
mentioning
confidence: 99%